Exploring Contextual and Behavioral Determinants of Environmental Auditing Adoption - Thu Hoai, Nguyen (Emerging Science Journal, 2025)
This study's primary objective is to identify the determinants of environmental auditing (EA) adoption intention in environmentally sensitive industries. Its novelty lies in developing and testing an integrated model that extends the Theory of Planned Behavior (TPB) by incorporating four contextual factors: Coercive Pressure, Stakeholder Pressure, Internal Resources, and Corporate Culture. For its methodology, the research analyzed survey data from 336 senior managers using Structural Equation Modeling (SEM). The findings confirm that the three core TPB constructs - Attitude, Subjective Norms, and Perceived Behavioral Control - are all direct, positive, and significant predictors of EA intention, with Attitude emerging as the strongest. Crucially, the study finds that the four contextual factors only influence intention indirectly, as their effects are fully mediated by the TPB constructs; Corporate Culture and Internal Resources exhibited the greatest total indirect effects. This research provides a significant improvement over existing models by empirically demonstrating this dual-pathway mechanism, suggesting that efforts to promote EA in Vietnam must focus not only on external pressures but also on cultivating positive managerial attitudes and enhancing internal organizational capabilities.